Does the Financial Characteristic Matters? Evidence from Firms Value on Banking Sector - Suryandari, Ni Nyoman Ayu; Mongan, Frischa Faradilla Arwinda (Institute of Computer Science (IOCS), 2025)
The purpose of this study is to ascertain how the value of banking businesses listed on the Indonesia Stock Exchange (IDX) for the years 2021–2023 is impacted by factors such as profitability, liquidity, solvency, company size, and growth. 135 banking businesses that were listed on the Indonesia Stock Exchange between 2021 and 2023 make up the study's sample. Purposive sampling was used to determine the sample. Multiple linear regression analysis is the method of analysis that is employed. The study's findings indicate that, among banking businesses listed on the Indonesia Stock Exchange (IDX) in 2021–2023, profitability, solvency, and company development positively impact company value, however liquidity and company size have no influence on firm value.